2007
DOI: 10.1007/s00104-007-1362-0
|View full text |Cite
|
Sign up to set email alerts
|

Kombinierte Nieren-Pankreas-Transplantation

Abstract: This is the first report of graft function after simultaneous pancreas-kidney transplantation looking specifically at gender differences with respect to donor and recipient. There was an increased risk of organ rejection of female donor organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…When analyzing donor-specific factors, no significant difference was found between patients receiving an organ from a male donor or a female donor. This is in contrast to a recent contribution by Schäffer et al [14] who reported significant differences correlated with sex, but this contribution focused on long-term survival and graft function and did not specifically analyze postoperative complications. In accordance with other authors [9,10], donor age significantly affected the prevalence of pancreasrelated complications, as well as the prevalence of complications with interventions.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…When analyzing donor-specific factors, no significant difference was found between patients receiving an organ from a male donor or a female donor. This is in contrast to a recent contribution by Schäffer et al [14] who reported significant differences correlated with sex, but this contribution focused on long-term survival and graft function and did not specifically analyze postoperative complications. In accordance with other authors [9,10], donor age significantly affected the prevalence of pancreasrelated complications, as well as the prevalence of complications with interventions.…”
Section: Discussioncontrasting
confidence: 74%
“…The mean age of donors was 34.1 years (range, 11-58 years). Based on a recent publication [11], the donors had a mean "preprocurement pancreas allocation suitability score (P-PASS) of 14 (range, [9][10][11][12][13][14][15][16][17][18][19]. The mean length of stay of the recipient in hospital starting with the transplantation and ending with the first discharge was 55 days (range, 21-219 days).…”
Section: Patientsmentioning
confidence: 99%
“…Colling and colleagues reported that recipient sex affected outcome after pancreas transplantation, and that a higher prevalence of early (<6 months) PGF was observed in women 15 . Schaffer and colleagues found an increased risk of organ rejection in female donors after pancreas transplantation 17 . To optimize organ utilization due to the severe shortage of donors worldwide, donor-related factors have been studied widely for their impact on graft function.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these reports looked only at the impact of donor sex or recipient sex. Also, the results of studies analyzing the influence of associations between donor sex and recipient sex on PGS in small-sample cohorts or in single-center studies have been contradictory 13 14 15 16 17 .…”
mentioning
confidence: 99%
“…Women had a greater risk for early graft failure compared to men after SPKT, caused by thrombosis and acute rejection at an earlier point in time. However, interestingly, the overall survival of pancreas grafts in women was similar to that in men [61,62]. Female recipients of male grafts currently have the best long-term outcome for renal and pancreatic graft function [62].…”
Section: Pancreas Transplantationmentioning
confidence: 99%